Penerapan Media Kartun dalam Pembelajaran IPA Fisika - Sa’dun Sa’dun; Sri Surachmi; Sri Utaminingsih (Peneliti.net, 2022)
This study aims to determine the difference in the effect of learning management using cartoon media with learning using conventional media on understanding physics concepts in class VIII junior high school students. This research was conducted from July 2022 to August 2022. The research method used was experimental research using a posttest only control group design model. The population of this study were students of class VIII SMP, with a sample of 30 students who were taken by using cluster random sampling technique. Data on understanding the concept of physics was obtained from a test of understanding the concept of physics with a total of 25 items that have been tested for validity, reliability, level of difficulty, and differentiating power of item questions. The data analysis technique used is t test analysis. Based on the output of the results of the t-test analysis, the following results were obtained: F = 0.027, then the Sig (2-tailed) result of 0.000 was found to be smaller than 0.05 (0.000 < 0.05) thus the first working hypothesis (Ha) which proposed reads